Recurrent Herpes Zoster Ophthalmicus Preceded by Anabolic Steroids and High-Dose L-Arginine - Stephen A. LoBue; Adam Goldman; Richard A. Giovane; Stacy M. Carlson; Michael Bivona; Sinan Albear; Thomas D. LoBue (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of a 34-year-old male with recurrent herpes zoster ophthalmicus (HZO) preceded by a 6-week cycle of anabolic steroids and high-dose amino acid supplementation. Case Presentation. A 34-year-old man presented to our institution for left eye pain for one week associated with a vesicular rash in the V1 dermatome, respecting the midline. The patient had no significant past medical or past ocular history, including systemic immunosuppressive agents or HIV. However, prior to the onset of his symptoms the patient had completed a 6-week course of anabolic steroids including trenbolone, deca-durabolin, and testosterone as well as high-dose arginine supplementation averaging more than 40 grams a day. The best-corrected vision was 20/25 OS with slit-lamp examination remarkable for punctate staining and pseudodendrites at 6 o’clock, outside the visual axis. The patient was treated with oral acyclovir 800 mg five times a day for seven days along with prednisolone QID and moxifloxacin QID which was tapered over a month. Four months after resolution, the patient developed a recurrent HZO keratitis preceded by another cycle of anabolic steroids and amino acid supplementation. Conclusion. In vitro L-arginine supplementation has been associated with the proliferation and virulence of a variety of herpes viruses. Anabolic steroids have also been demonstrated by various studies to negatively affect cell-mediated immunity necessary to prevent viral infection. Thus, it is possible that anabolic steroids in conjunction with increased L-arginine intake may have precipitated a recurrent HZO in a previously healthy, immunocompetent individual.